A novel combined severe plastic deformation method for producing thin-walled ultrafine grained cylindrical tubes - Abdolvand, H.; Sohrabi, H.; Faraji, G.; Yusof, F. (Elsevier, 2015)
A novel severe plastic deformation (SPD) process entitled combined parallel tubular channel angular pressing (PTCAP) and tube backward extrusion (TBE) is proposed for producing thin-walled ultrafine-grained (UFG) tubes. In this new combined SPD approach, the PTCAP and TBE processes are consequently applied to the tube material in which a severe plastic strain is applied to produce a UFG thin-walled tube. This technique was performed on an AZ31 magnesium tube, and a remarkable grain refinement was achieved. The results showed that this method could easily produce a high strength thin walled tube. The microhardness increased significantly to 70 HV after the process from an initial value of 38 HV. (C) 2014 Elsevier B.V. All rights reserved.